Upaya Konservasi Tanah dan Air pada Daerah Pertanian Dataran Tinggi di Sub-Daerah Aliran Sungai Gandul - diah auliyani (Jurnal Ilmu Pertanian Indonesia, 2020)
Land susceptibility to degradation is characterized by the loss of topsoil due to erosion which is considered as a threat to agricultural productivity. Information about land sensitivity to erosion is crucial in determining the appropriate soil and water conservation techniques to avoid land degradation. This study, which was located in the Gandul Sub-Watershed, aims to analyze the level of land sensitivity to erosion in highland agricultural areas. Data analysis was carried out spatially using land system and land-cover maps. Soil and water conservation efforts were determined based on the land function and sensitivity. The land sensitivity to erosion in the Gandul Sub-watershed was categorized into 3 levels which were moderate (3.9%), high (95%), and very high (0.8%). There were various directions for Gandul Sub-Watershed management by considering the level of sensitivity of the land and the function of the area. Creating a ridge is one of the soils and water conservation practices that has been implemented for a long time by local communities as a soil erosion prevention. Keywords: agriculture, erosion, Gandul, sensitivity